SEISMIC OBSERVATION WITH LOCAL TELEMETRY NETWORK AROUND SYOWA STATION, EAST ANTARCTICA - アカマツ, ジュンペイ; イチカワ, ノブオ; カミヌマ, カツタダ; AKAMATSU, Junpei; ICHIKAWA, Nobuo; KAMINUMA, Katsutada (National Institute of Polar Research, 1989)
P(論文) A local telemetry seismic network was established around Syowa Station to study local seismicity and characteristics of seismic waves in the Lutzow-Holm Bay and Prince Olav Coast region, East Antarctica. The observation system utilizes an event detection algorithm for monitoring small earthquakes by coping with noise condition peculiar to Antarctica. More than 4400 events were recorded during the period from June 1987 to January 1988. Most of them were icequakes and continuous vibrations caused by glacier movements. However, 477 earthquakes were identified. Several shallow crustal earthquakes with S-P times of 5-6 s and 20 s are located around Syowa Station, near possible faults inferred from surface topography and geology. Although the East Antarctic shield has long been considered to be an aseismic area, local earthquakes occur under some tectonic condition. departmental bulletin paper